Oviposition Deterrence and Ovicidal Activity of Birbira (Melletia furrgunia) on Diamondback Moth (Plutella xylostella) (Lepidoptera: Plutellidae) - Nega, Adem; Mulatu, Bayeh (International Research Journal of Insect Sciences, 2021)
The efficacy of different polar and non-polar solvent extracts of Birbira, Melletia furrginea (Hochst.) Baker tree seeds namely: Water, Acetic acid, Acetone, Chloroform, Toluene, and Hexane at different rates were evaluated on Diamondback moth, Plutella xylostella L. oviposition and egg mortality under laboratory conditions. The leaf dipping method was used to run both assays. In the assay, full Oviposition deterrence was recorded at the higher rates of polar solvent extracts. Significantly higher egg un-hatchability was recorded only at the higher rates for non-polar extracts. Eggs mortality caused by extracts with Water and Acetone was very high, and have much smaller LC50 values. In contrast, LC50 was higher for the other extracts. However, there was a constant increase in the percent kill of egg mass with the increase in the extract concentration. From this study, it is evident that M. furrgunia extracts with different solvents possess significant oviposition deterrence and ovicidal effect on P. xylostella.